Quantifying systemic vulnerability of interdependent critical infrastructure networks: A case study for volcanic hazards - Weir AM; Wilson TM; Bebbington MS; Campbell-Smart C; Williams JH; Fairclough R (Elsevier Ltd., 2024)
Infrastructure networks are vital for the communities and industries that rely on their continued operation. Disasters stress these complex networks and can provoke systemic disruptions that extend far beyond the spatial footprint of hazards. An enduring challenge for assessing infrastructure networks within disaster impact assessment frameworks has been to adequately quantify the high spatial interdependence of these networks, and to consider risk management interventions through time. This is of particular importance for volcanic eruptions, which can produce multiple hazards over highly variable spatiotemporal extents. In this study, we present a methodology for the quantification of systemic vulnerability of infrastructure networks, which can be coupled with physical vulnerability models for the purpose of impact assessment. The two-part methodology first quantifies the haard-agnostic criticality of infrastructural components, inclusive of interdependencies, and then incorporates representative hazard spatial footprints to derive the systemic vulnerability. We demonstrate this methodology using the case study of volcanic eruptions from Taranaki Mounga volcano, Aotearoa New Zealand, where there are many industrial sites of national importance, and a high likelihood of a complex multi-hazard volcanic eruption. We find a considerable increase in the systemic vulnerability of electricity and natural gas network components after incorporating infrastructure interdependencies, and a further increase in the systemic vulnerability of these critical components when cross-referenced with potential volcanic hazard spatial extent. The methodology of this study can be applied to other areas of interest in both its hazard-agnostic or hazard-dependent form, and the systemic vulnerability quantification should be incorporated into impact assessment frameworks.
Keywords: Volcanic multi-hazards; Impact assessment; Disaster risk assessment; Interdependencies; Criticality; Volcanic risk management